Personality Dispositions, Resilience, and Decision Making and Their Impact on Psychological Well-Being of Management Graduates - Venkatesan, M.; Rohatgi, Anubha (Prabandhan: Indian Journal of Management, 2018)
Business organizations are constantly facing a lot of challenges from political, environmental, social, technological, economic, and legal environments and these organizational level challenges and their changes as well are increasing many folds in the recent times. This present state is placing undue pressure on managers, especially young managers. As a result, managers are experiencing changes in their physical, psychological, cognitive, emotional, and social environments, which has a significant impact on their psychological well-being. In order to see the impact of personality dispositions, resilience, and decision making on psychological well-being of management graduates, this study was undertaken ; 120 management students participated in the study, out of which 78 students completed the tests. The tools used were MBTI by Briggs and Myers (1998), FIRO-B by Waterman and Rogers (2004), Resilience scale by Wagnild and Young (1993), Decision Making Style Inventory by Rowe and Mason (1987), and Psychological Well-being scale by Ryff (1989). The analysis of data revealed that most of the dimensions of personality disposition, resilience, and decision making were found to be significantly correlated with psychological well-being. The study results showed that personality dispositions, resilience, and decision making were significant predictors of psychological well-being. The gender of management graduates showed significant variation in thinking and feeling dimensions of personality dispositions, and autonomy dimension of psychological well-being. The work experience of management graduates varied significantly onÂ some dimensions of personality dispositions. Similarly, the age of management graduates was also found to differ significantly on some dimensions of personality dispositions and psychological well-being.